Professional skills and competencies required of accountants : what are the requirements for employment advertisements? - Lira, Thais Alves (2021)
The research aims to analyze the patterns of similarities of skills and abilities signaled in job advertisements for an accountant position, from the guidelines of the International Federation of Accountants (IFAC), under the light of signaling theory. To achieve the objective, a content analysis was carried out on 200 job advertisements for an accountant position on the “Catho” and “LinkedIn” websites. Through descriptive statistics, the competencies and skills most demanded by the market were identified and later, with cluster analysis, the advertisements from different organizations were grouped. The study shows, as requirements for hiring, professionals who demonstrate, in addition to the technical skills exclusive to Accountants, emerging skills, such as critical thinking, problem solving and teamwork. Three job profiles were highlighted based on the competencies/skills that companies require when hiring accountants: languages; financial reporting and taxation, accounting management. The contribution of this research is to provide institutions, educators and professionals in the area, with insights into the requirements demanded by the job market for accounting professionals, and they can use this information for a constant professional update, aiming to meet the real needs of companies.